Reinsurance market in the Republic of Kazakhstan: state and development prospects . - Vorobyova, S.M.; Murzina, M.O. (BUKETOV BUSINESS REVIEW, 2017)
As a result of the study, the authors concluded that there is no professional reinsurance sector in Kazakhstan and reinsurance operations are conducted with the participation of foreign insurance and reinsurance companies, foreign brokers, and between national insurance companies on terms of reciprocity. Analysis of reinsurance operations conducted in the country showed that there is a «export» of currency abroad through reinsurance channels. At the first stages of development of the reinsurance market, this occurred as a result of the transfer of reinsurance premiums to foreign reinsurers in the absence of major risks. As an insurance compensation, a small amount of the transferred insurance premiums returned to the country. At the present stage of development of the reinsurance market, it became possible to export currency also due to incoming reinsurance, when payments of insurance compensation of domestic reinsurers significantly exceed the received premiums under reinsurance contracts. If there is a stable tendency of high participation in the settlement of losses on the part of Kazakhstan insurers, we can talk about their non-professionalism in assessing the results of reinsurance. In order to reduce the outflow of insurance premiums from the territory of the country and increase the capacity of the national insurance market, it is advisable for the largest insurance organizations of the Republic of Kazakhstan to create an insurance or reinsurance pool, to integrate into a single international insurance and reinsurance space within the framework of the Eurasian Economic Community, and thereby significantly change the current situation Domestic reinsurance market.